Equal Sums of Two $k$th Powers - Browning, T (Elsevier, 2002)
Let k ≥ 5 be an integer, and let x ≥ 1 be an arbitrary real number. We derive a bound Oε,k (x2/3k+ε + x3/k√k+2/k(k-1)+ε), for the number of positive integers less than or equal to x which can be represented as a sum of two non-negative coprime kth powers, in essentially more than one way.